Blossom the flower girl fairy - Meadows, Daisy (Meadows, Daisy. Rainbow magic special edition., 2016)
"Here comes the bride! Rachel's aunt Angela is a talented wedding planner. She's organizing the biggest wedding Tippington has ever seen--and she needs Rachel and Kirsty's help. Rachel and Kirsty are put in charge of the bride's flower girls. When Jack Frost shows up uninvited, the wedding is at risk. Luckily for everyone, Blossom the Flower Girl Fairy has a very special kind of magic--and she's determined to make sure this wedding goes off without a hitch!"--